The FAS-receptors of apoptosis expression on the medulloblastomas cells - Orlov, Yu. A.; Lisyany, A. N.; Shaversky, A. V.; Malysheva, T. A.; Chernenko, O. G.; Primushko, L. I. (Ukrainian Neurosurgical Journal, 2005)
The Fas-receptor of apoptosis expression on the living medulloblastomas cells was determined. Fas-receptor of apoptosis was expressed on 4–48,8% tumors cells. The histological features and size of tumors did not influence on the Fas-receptor expression, just the age of patients defined on the expression level. The medulloblastomas tissue infiltration with lymphocytes was not considerable and didn’t influence on the Fas-receptor expression on the tumors cells.